2017
DOI: 10.3390/en10030298
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals and Polycyclic Aromatic Hydrocarbons in Urban Leaf Litter Designated for Combustion

Abstract: Vast amounts of leaf litter have to be disposed of by city administrations. This biomass has the potential for energy conversion, but contamination with pollutants can adversely affect this usage. We investigated leaf litter samples from the city of Kassel by analyzing their heavy metal and polycyclic aromatic hydrocarbon (PAH) concentrations. Leaf samples were indeed contaminated with heavy metals and PAHs and contamination was influenced by provenience and collection technique. A simple cleaning system of wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…The results of the current study showed that the individual PAHs concentrations were attributed to combustion activities, due to the predominance of low molecular weight PAHs (with 2–3 ring PAHs) in the two factories which arise from un-combusted petroleum products and combustion processes. These results were in agreement with Nitsche et al ( 2017 ) who found that LMW-PAHs originated from low-temperature combustion processes, while HMW-PAHs result from high-temperature combustion processes. In addition, Patel et al ( 2020 ) stated that incomplete combustion is the main source of PAH emissions by various industrial activities such as aluminum production.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the current study showed that the individual PAHs concentrations were attributed to combustion activities, due to the predominance of low molecular weight PAHs (with 2–3 ring PAHs) in the two factories which arise from un-combusted petroleum products and combustion processes. These results were in agreement with Nitsche et al ( 2017 ) who found that LMW-PAHs originated from low-temperature combustion processes, while HMW-PAHs result from high-temperature combustion processes. In addition, Patel et al ( 2020 ) stated that incomplete combustion is the main source of PAH emissions by various industrial activities such as aluminum production.…”
Section: Discussionsupporting
confidence: 93%
“…In this study ratios were 0.8 and 1.2.Meanwhile, high molecular weights PAHs (HMW-PAHs) are usually released from pyrogenic sources including coal combustion and vehicular emissions(Kumar et al, 2020). The results of the present study were in agreement withNitsche et al (2017), which indicated that LMW-PAHs were mostly originated from low-temperature combustion processes. While, HMW-PAHs were mostly originated from high-temperature combustion processes (such as industrial activities or combustion of agriculture wastes).An earlier studies found a debate about occupational exposure to BAP; as a higher risk for development of fatal ischemic heart disease.…”
supporting
confidence: 75%
“…As a third possible explanation for the increased Cu and Fe concentrations in the press cake, it has to be considered that these elements might not be released as easy as the other minerals into the press fluid and might be retained in the solid phase. However, bare washing of leaf litter biomass showed a clear decrease in Cu concentration [16]. Additional research is required to fully understand why Fe and Cu concentrations increase in the press cake.…”
Section: Elemental Composition Of Silage and Press Cakementioning
confidence: 99%
“…Two replicates of pure inoculum were digested separately to subtract the methane yield of the inoculum from the total methane produced in inoculated samples and thereby calculate the actual yield from the sample. Biogas was collected in gas-proof bags, and volume was measured with a wet drum gas meter (TG5; Ritter Apparatebau GmbH, Bochum, Germany) at Digestion Days 1,2,3,4,7,9,11,14,16,18,and 21 for press fluids and additionally on Days 24, 28, 31 and 35 for silage. While digesting, samples were stirred every 3 h for 15 min with a U-shaped stirrer driven by a 12 V direct current motor.…”
Section: Anaerobic Digestionmentioning
confidence: 99%